Optimization of protective agents for freeze drying of Paenibacillus polymyxa Kp10 live cells - Nasran, Hayatun Syamila (2018)
In recent years, biocontrols have been considered to be used in inhibiting pests and pathogens to enhance plant growth performance in agriculture sector. This is due to concerns about usage of chemical fungicides for controlling fungal pathogens that may produce bad effects on environments such as contaminating ground waters with chemical residues and polluting soil for crops. Effects of the chemical fungicides also bring harmful to human as users and consumers of crops fields. Biofungicides for fungal pathogens in plant crops are normally kept in farm at room temperature and this condition may reduce viability of microorganism during storage. Protective agent application during freeze drying of the microorganism could improve survival of the culture throughout the freeze drying process. In this study, freeze drying was chosen as a technique for preservation and protective agent formulation was determined to improve viability of Paenibacillus polymyxa Kp10 after freeze drying by using response surface methodology (RSM). A five-level, three-variable central composite design (CCD) was used to evaluate the effects of skim milk, lactose and sucrose as protective agents on the viability of P. polymyxa Kp10 due to freeze drying. Paenibacillus polymyxa Kp10 was screened for its potential in inhibiting fungal pathogens as biofungicides using fresh and freeze dried culture. Fresh and freeze dried strain was tested with food-borne pathogen to indicate its antimicrobial activity. 5% (v/v) was chosen as inoculum size and the highest cell production was at 22 h. Optimum combination of protective agents analysed by RSM was 20% (w/v) skim milk, 10% (w/v) lactose and 27.5% (w/v) sucrose for freeze drying process of P. polymyxa Kp10. The predicted value for cell viability obtained was 5.833 log CFU/ml under the optimum combination after freeze drying process. This value was slightly different to the experimental value (5.452 log CFU/ ml). P. polymyxa Kp10 were found to inhibit Colletrichum gloeosporioides and C. truncatum through dual culture test with percentage of inhibition of radial growth (PIRG) at 60.11% and 62.8%, respectively. Freeze dried P. polymyxa Kp10 inhibited C. gloeosporioides and C. truncatum at 66.52% and 60.18%, respectively. For antimicrobial activity, the result showed that the activity reduced by 43.6% from 4930.56±0.04 AU/ mL to 2780.94±0.05 AU/ mL after freeze drying of P. polymyxa Kp10. Thus, P.polymyxa Kp10 can be freeze dried with the combination of protective agents and its activity showed stability after the freeze drying process.